The magic cocktail: Ampicillin and Biosynthesized gold nanoparticles synergism against Staphylococcus aureus - Oliveira, Marco (2023)
Gold nanoparticles (AuNPs) have garnered attention as a potential alternative to conventional antibiotics due to their innovative antibacterial properties. This study demonstrates the successful production of biosynthetic gold nanoparticles (bAuNPs) using Pseudomonas aeruginosa (P. aeruginosa) as spherical nanostructures at 58 ◦C for 24 h, under alkaline pH (9.0). The successful synthesis of bAuNPs was confirmed through UV-Vis spectroscopy, exhibiting a characteristic peak within the 500–600 nm wavelength range, and the evaluation of the main functional groups and morphology were stressed by Fourier Transform Infrared Spectroscopy (FT-IR) and Transmission Electron Microscopy (TEM), respectively. Subsequently, the synthesized bAuNPs were combined with low concentrations of ampicillin and evaluated against Methicillin-Susceptible Staphylococcus aureus (MSSA) and Methicillin-Resistant Staphylococcus aureus (MRSA) through the classical serial dilution method. This innovative approach holds the potential to address the escalating issue of antibiotic resistance, providing a viable and sustainable solution